Efficient, rapid, and regioselective bromination of anilines and phenols with 1-butyl-3-methylpyridinium tribromide as a new reagent/solvent under mild conditions - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Tetrahedron Letters, 2009)
1-Butyl-3-methylpyridinium tribromide, [BMPy]Br(3) proves to be a highly efficient, regioselective reagent/solvent for nuclear bromination of various anilines and phenols. The synthesis and characterization of the room temperature ionic liquid [BMPy]Br(3) (2) is described. The bromination was carried out in the absence of organic solvents and in most cases the only extraction solvent needed was water. The spent 1-butyl-3-methylpyridinium bromide (1) was easily recycled. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bromination; Ionic liquid; Regioselective; [BMPy]Br(3)

Mild, efficient, and regioselective monobromination of arylamines and phenols using [BBIm]Br-3 as a new reagent - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Synthetic Communications, 2010)
We report here an efficient method for the synthesis and characterization of the room-temperature ionic liquid 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3) (2) and its application as an efficient reagent and solvent for regioselective bromination of arylamines and phenols under mild conditions. The bromination was carried out in the absence of organic solvents, and in most cases, the only extraction solvent needed was water. The spent 1,3-di-n-butylimidazolium bromide (1) was easily recycled.
Keywords: Ionic liquid; monobromination; Regioselective; Solvent-free; [BBIm]Br3

N-nitrosation of secondary amines using p-TSA-NaNO2 as a novel nitrosating agent under mild conditions - Borikar, Sanjay P.; Paul, Vincent (Synthetic Communications, 2010)
A combination of p-toluenesulfonic acid (p-TSA) and sodium nitrite was used as a novel effective nitrosating agent for the N-nitrosation of secondary amines to their corresponding nitroso derivatives under mild and heterogeneous conditions in moderate to excellent yields.
Keywords: N-nitrosation; nitroso amines; p-toluenesulfonic acid; secondary amines

Aromatic bromination of aldehydes and ketones using 1,3-di-n-butylimidazolium tribromide [BBIm]Br3 ionic liquids under solvent-free conditions - Borikar, Sanjay P.; Daniel, Thomas (Journal of the Iranian Chemical Society, 2011)
An environmentally benign and efficient process for the preparation of monobromo derivatives of aryl aldehydes and ketones was developed by simple and practical reactions of aryl aldehydes or ketones with 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3), as a brominating reagent under solvent-free conditions in very high yields. The process has several advantages: high conversions, short reaction time, mild reaction conditions, simple workup with good to quantitative yields and re-usable ionic liquid.
Keywords: Bromination; green chemistry; Ionic liquid; Solvent-free; [BBIm]Br-3

Convenient and efficient protocol for the synthesis of acylals catalyzed by bronsted acidic ionic liquids under ultrasonic irradiation - Borikar, Sanjay P.; Daniel, Thomas (Ultrasonics Sonochemistry, 2011)
The synthesis of acylals (1,1-diacetates) via the reactions of aldehydes with acetic anhydride was carried Out in 85-97% yields at room temperature under ultrasound irradiation catalyzed by the Bronsted acidic ionic liquid [bmpy]HSO(4). This method provides several advantages, such as solvent-free conditions, operational simplicity, higher yields, and reduced environmental consequences. The ionic liquid was recovered and reused. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Butyl-3-methylpyridinium hydrogen sulfate; 1-Diacetates; Acylals; Ionic liquid; Solvent-free; Ultrasonic irradiation

First total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one: a cancer chemopreventive agent - Borikar, Sanjay P.; Paul, Vincent; Puranik, Vedavati G.; Sathe, Vilas T.; Lagunas-Rivera, Selene; Ordonez, Mario (Synthesis-Stuttgart, 2011)
The first total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one, a newly discovered natural product with anticancer property is described by two different routes. A sequence involving an incorporation of a methyl group via a Gilman reagent and a chemoselective reduction of a cyclic anhydride functionality are the key steps. The methods proposed start from easily available starting materials and allow ready preparation of the final compound in good overall yield.
Keywords: Allium cepa; chemopreventive; Gilman reagent; selective; synthesis

Differential transcriptional activity of SAD, FAD2 and FAD3 desaturase genes in developing seeds of linseed contributes to varietal variation in alpha-linolenic acid content - Rajwade, Ashwini V.; Kadoo, Narendra Y.; Borikar, Sanjay P.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Phytochemistry, 2014)
Linseed or flax (Linum usitatissimum L.) varieties differ markedly in their seed a-linolenic acid (ALA) levels. Fatty acid desaturases play a key role in accumulating ALA in seed. We performed fatty acid (FA) profiling of various seed developmental stages of ten Indian linseed varieties including one mutant variety. Depending on their ALA contents, these varieties were grouped under high ALA and low ALA groups. Transcript profiling of six microsomal desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B), which act sequentially in the fatty acid desaturation pathway, was performed using real-time PCR. We observed gene specific as well as temporal expression pattern for all the desaturases and their differential expression profiles corresponded well with the variation in FA accumulation in the two groups. Our study points to efficient conversion of intermediate FAs [stearic (SA), oleic (OA) and linoleic acids (LA)] to the final product, ALA, due to efficient action of all the desaturases in high ALA group. While in the low ALA group, even though the initial conversion up to OA was efficient, later conversions up to ALA seemed to be inefficient, leading to higher accumulation of OA and LA instead of ALA. We sequenced the six desaturase genes from the ten varieties and observed that variation in the amino acid (AA) sequences of desaturases was not responsible for differential ALA accumulation, except in the mutant variety TL23 with very low (<2%) ALA content. In TL23, a point mutation in the FAD3A gene resulted into a premature stop codon generating a truncated protein with 291 AA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ALA; Fatty acid desaturases; Fatty acids; Flax; Gene expression; Linseed

Synthesis of non-toxic triethyl citrate plasticizer by esterification of renewable citric acid using modified zeolite - Nandiwale, Kakasaheb Y.; Borikar, Sanjay P.; Bokade, Vijay V. (Clean-Soil Air Water, 2015)
Triethyl citrate (TEC), a non-toxic plasticizer, was synthesized by esterification of renewable citric acid (CA, from entire waste of oranges) with ethanol over modified H-ZSM-5 (HZ-5) zeolite. Different micro-meso composites (M-HZ-5) with varying crystallinities were prepared by alkaline treatment of HZ-5. M-HZ-5(0.6) (87% crystallinity) was observed to be a potential and environmentally benign catalyst with 96% CA conversion, 64% TEC selectivity (61.44% TEC yield), and a reusability of six cycles. The probable catalytic mechanism of esterification was also proposed.
Keywords: Biowaste; Catalysts; green chemistry; Micro-mesopre composites; reusability